Factors that Could Increase Mortality in Patients with H1N1 - Tutak, Ayse Sahin; Celik, Ramazan; Sayiner, Hakan Sezgin; Tutak, Atilla (Archives of Clinical and Medical Case Reports, 2018)
Objective: In this study, clinical and vital parameters of 5 patients who were being followed up at intensive care unit due to H1N1 were retrospectively analyzed and the clinical findings that should not be overlooked were stressed. Method: Clinical follow ups of 5 patients whose H1N1 diagnoses were verified with PCR technique were recorded by the attending physician and vital parameters were recorded from patient files and an overall assessment was done. Results: Oxygen saturation of 4 out of 5 patients whose mean age was 48 years (range 43-59) was less than or equal to 85% on admission and all of four died. Symptoms had begun 4-5 days before admission in 3 of these dying patients, exact data could not be obtained in another patient due to mental retardation. Oxygen saturation of the only surviving patient was 91% on admission and symptoms had begun one day ago. All patients had an accompanying disease and one had pregnancy. A significant improvement was observed on chest X-rays of 2 out of 4 dying patients, a significant radiological improvement was not detected in the forth case as the patient died within 36 hours, whether an improvement was obtained was not evaluated with X-ray in the third patient as she was pregnant. Gastric drainage was present in the first 3 dying patients. The forth case could not be completely evaluated as he/she died early. Conclusion: The day of treatment commencement and presence of an accompanying disease were found as important factors for influenza-related mortality and we suggest that central nervous system (CNS) should be evaluated in patients whose clinical condition does not improve despite radiological improvement. In addition, blood drug level should be examined to see whether absorption is sufficient in case of high amounts of gastric drainage for providing an effective treatment. <gdiv></gdiv>